The Sociomaterial Negotiation of Social Entrepreneurs' Meaningful Work. (18th December 2018) - Symon, Gillian; Whiting, Rebecca
Abstract: This research examines the role of digital technology in the constitution of meaningful work. Adopting a sociomaterial perspective, we argue that meaningful work emerges as an outcome of a complex negotiation between individuals and their digital devices. This process was explored through video diaries and interviews with social entrepreneurs, capturing moments of their everyday meaning‐making and encouraging reflexivity. Accounting for their sociomaterial practice led participants to reaffirm their work as uniquely meaningful, produce more nuanced accounts of meaningfulness and/or make pragmatic adjustments to their meaning making. Whilst authenticity was a key meta‐narrative in these accounts, it also produced tensional knots which, in their unravelling, required the adoption of more practicable meanings of work. The paper concludes by urging scholars to de‐centre the human from their analysis to provide a more complete account of meaningful work.